PENGARUH VARIASI KONSENTRASI NaOH TERHADAP SIFAT FISIK SABUN PADAT EKSTRAK UBI JALAR UNGU (Ipomoea batatas Lam) - Dewi Riskha Nurmalasari; Vira Ananda Putri; Dewi Rashati (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Soap is a cleanser made by reacting chemically between a sodium base and a fatty acid. NaOH is varied because it is the main ingredient in the saponification process. This study aims to determine the effect of variations in NaOH concentration on the physical properties of solid soap preparations of purple sweet potato extract (Ipomoea batatas Lam.). The research method used is a pre-experimental one group post test design. The carrier material used in this study was NaOH with different concentrations of F1 (5%), F2 (8.5%), F3 (12%). The active ingredient used in this study was purple sweet potato extract as an antioxidant. Evaluation includes organoleptic (texture, color, smell), pH, moisture content, and foam height. The results showed that changes in NaOH concentration had an effect on the organoleptic physical properties of texture, pH, water content, and foam height of solid soap preparations and did not affect the organoleptic color and smell. The formula with 8.5% NaOH concentration gave the best physical characteristics in terms of organoleptic, namely smooth texture, light brown color, strong bubble gum smell, pH 9.9, water content 0.5%, high foam in 9 cm aquadest.